Curing Condition and NaOH Concentration on the Mechanical Properties of Fly Ash Based Geopolymer Mortars - Zhang, Zheng; Huo, Zhiqiang; Zhengxun, Yang; Wang, Xu; Xia, Jingang (International Journal of Sustainable Construction Engineering and Technology, 2023)
This paper describes the effect of different curing conditions on the mechanical properties of fly ash-based geopolymer mortars activated by different NaOH solution molarity. The influence of different curing initial curing temperatures (40?,50?,60?), initial curing time (4h,8h,12h), and NaOH solution concentration (8mol, 10mol, 12mol) was studied by orthogonal design and the single-variable method. Results indicated that the fluidity of the geopolymer mortar sample followed the opposite trend with NaOH molarity increase. The most sensitive factor is NaOH molarity without considering curing age based on the data from orthogonal experiments. Furthermore, the study revealed a tendency to increase the flexural and compressive strength with rising NaOH concentration, initial curing temperature, and time, despite the mechanical strength development speed at different ages being various, and the optimum NaOH molarity may be 10mol while NaOH pellets dosage and CO2 emission were considered.